Green optical orthogonal frequency‐division multiplexing networks. Issue 3 (1st June 2014) - El‐Gorashi, Taisir E.H.; Dong, Xiaowen; Elmirghani, Jaafar M.H.
Abstract : Orthogonal frequency‐division multiplexing (OFDM) has been proposed as an enabling technique for elastic optical networks to support heterogeneous traffic demands by enabling rate and modulation adaptive bandwidth allocation. The authors investigate the energy efficiency of optical OFDM‐based networks. A mixed integer linear programming model is developed to minimise the total power consumption of rate and modulation adaptive optical OFDM networks. Considering a symmetric traffic, the results show that optical OFDM‐based networks can save up to 31% of the total network power consumption compared to conventional Internet protocol over wavelength division multiplexing (WDM) networks. Considering the power consumption of the optical layer, the optical OFDM‐based network saves up to 55% of the optical layer power consumption. The results also show that under an asymmetric traffic scenario, where more traffic is destined to or originates from popular nodes, for example data centres, the power savings achieved by the optical OFDM‐based networks are limited as the higher traffic demands to and from data centres reduce the bandwidth wastage associated with conventional WDM networks. Furthermore, the achievable power savings through data compression have been investigated, considering an optical OFDM‐based network.